Lima in three works by José María Arguedas: From "extranguera" city to cultural encirclement - Paredes Laos, Jorge (2021)
The objective of this article is to identify the presence of Lima and migration in three works by José María Arguedas, published between 1941 and 1964: Yawar Fiesta, Todas las sangres, and A Nuestro padre creator Túpac Amaru (himno-canción). Works released in a 25-year time frame that correspond to Arguedas’ greatest creative moment and also when the migration from the countryside to Lima occurred with greater intensity. I seek to demonstrate how Lima and the figure of the migrant is transformed into the poetics of Arguedas: in his first novel Yawar Fiesta (1941) the capital appears as that distant, foreign world that exists behind the mountain range, to which the community members of Lucanas they go down a path of their own making to establish themselves and shape the new ‘neighborhoods’ or departmental clubs. Later, in Todas las sangres, (1964), Lima is again an echo drawn from the objectives of the character Demetrio Rendón Willka, someone who after spending time in the capital returns to his hometown, with other customs. As the novel progresses, Lima will gain more and more prominence as the space to which Indians and lords flee before the disintegration of the world represented in fiction. And, finally, the vision of Lima and the migration represented in A nuestro padre creador Túpac Amaru (himno-canción) (1962), as a cultural siege to the city of the lords, without ceasing to perceive the melancholic feeling for the tear and transculturation.